Evaluation of Bio-red Pigment Extraction from Monascus purpureus FTC5357 - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; F., Said; M., Ramu; N. M. H., Yasin (IOP Publishing, 2020)
A suitable extraction technique helps to increase the extraction yield and stimulate higher quality of pigments. Therefore, investigating the effect of different extraction solvents on red pigment produced via solid-state fermentation (SSF) by Monascus purpureus FTC 5357 are essential. In this study, oil palm frond (OPF) was used as a substrate for the fermentation process. The fermentation was conducted at 30 °C for eight days. Variation of solvents (95% ethanol, 60% ethanol and distilled water), pH and time of extractions were applied on the fermented product. The extracted pigment was then analysed using spectrophotometer at 500 nm, for red pigment. Combination of pH 6 and 60% ethanol at 16 h pronounced to be the best conditions to extract the pigment, with an absorbance value of 207 AU/g.d. The advantage of the ethanol as a solvent extraction is cheap and non-toxic. Later, the extracted pigment is safe to be used in food applications.